Sexual offending by strangers - Greenall, Paul V. (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Exploring a specific type of sexual violence committed by a specific type of sexual offender, namely adult male on adult female stranger sexual violence, this book provides readers with an enhanced understanding of both the offences being committed and the offenders who commit them. Although acts of serious stranger sexual violence are rare, they are important as they occur in the context of there being no pre-existing relationship between the offender and victim, meaning they present significant challenges to criminal justice practitioners who are required to investigate, assess and understand such offending. Arguing for the importance of adopting an ideographic perspective, this book encourages readers to draw upon a variety of different theories and models as appropriate, such as considering the impact of a behavioural conditioning process, or sexual violence as a manifestation of prior learning or early life experiences. Divided into four sections, this comprehensive volume guides the reader through key concepts, different types of stranger sexual violence, and applications to criminal justice practice. Sexual Offending by Strangers will be of use to police officers, prison officers, and practitioners working with offenders in either secure or community settings. It will also be of value to students and scholars researching the topic of sexual violence"--
Keywords: Sex crimes; Sex offenders; Criminal justice, Administration of; PSYCHOLOGY / Forensic Psychology; SOCIAL SCIENCE / Criminology